2020
DOI: 10.21203/rs.3.rs-44152/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Soil origin and plant genotype structure distinct microbiome compartments in the model legume Medicago truncatula

Abstract: Background Understanding the genetic and environmental factors that structure plant microbiomes is necessary for leveraging these interactions to address critical needs in agriculture, conservation, and sustainability. Legumes, which form root nodule symbioses with nitrogen-fixing rhizobia, have served as model plants for understanding the genetics and evolution of beneficial plant-microbe interactions for decades, and thus have added value as models of plant-microbiome interactions. Here we use a common gard… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 116 publications
(155 reference statements)
4
25
2
Order By: Relevance
“…Fungal endophytes can facilitate mineral nutrient uptake, promote plant growth and development, and induce defence resistance against pathogens (Taghinasab et al ., 2018). In a previous Medicago truncatula study, LEfSe analyses identified the following: 10 biomarkers OTUs for leaves dominated by Pseudomonas , Niastella and Phormidium ; and 12 biomarker OTUs for roots dominated by Thioalkalibacter , Neorhizobium and Ohtaekwangia , plus one OTU ( Ensifer ) for nodules (Brown et al ., 2020). These results indicated that different parts of P .…”
Section: Discussionmentioning
confidence: 99%
“…Fungal endophytes can facilitate mineral nutrient uptake, promote plant growth and development, and induce defence resistance against pathogens (Taghinasab et al ., 2018). In a previous Medicago truncatula study, LEfSe analyses identified the following: 10 biomarkers OTUs for leaves dominated by Pseudomonas , Niastella and Phormidium ; and 12 biomarker OTUs for roots dominated by Thioalkalibacter , Neorhizobium and Ohtaekwangia , plus one OTU ( Ensifer ) for nodules (Brown et al ., 2020). These results indicated that different parts of P .…”
Section: Discussionmentioning
confidence: 99%
“…Soil is the main influencing factor on the rhizosphere, root, or nodule microbiomes in non-legumes (43) (44) and legumes, such as Medicago truncatula (45) and soybean (46,47). However, many of these studies cite vast differences in the diversity of the microbial communities or physicochemical properties of the soil inputs as the reason for the disparity in plant microbiomes (43,45,47). Our results showed that the nodule microbiomes of plants inoculated with different soil suspensions varied significantly (Table S3).…”
Section: Soil Suspension Inoculum Influences Lotus Spp Nodule Microbiomementioning
confidence: 99%
“…Plant genotype influence on plant-related microbiomes varies among legume species. Brown et al, reported that the rhizosphere microbial community of M. truncatula is mainly influenced by soil type, while the host genotype is the main determinant of the microbiota in internal plant compartments (45). Similarly, the nodule microbiome of soybean and alfalfa are primarily influenced by host genotype, while the rhizosphere microbiome is more regulated by soil type (52).…”
Section: Soil Suspension Inoculum Influences Lotus Spp Nodule Microbiomementioning
confidence: 99%
“…They can live in neutral, beneficial or pathogenic interaction within or outside of the plant (Raaijmakers et al ., 2009; Turner et al ., 2013a). Unsurprisingly, in addition to environmental niche effects and edaphic factors, plants have evolved mechanisms to shape such communities, benefit from and even exploit microbiomes as a huge genetic resource to expand their ability to cope with changing environmental conditions (Bulgarelli et al ., 2012; Lundberg et al ., 2012; Philippot et al ., 2013; Reinhold‐Hurek et al ., 2015; Liu et al ., 2019; Brown et al ., 2020). The ability of plant roots to modify microbial communities is strongest in the endosphere but can reach well beyond the rhizosphere.…”
Section: Introductionmentioning
confidence: 99%